Study on negative friction of pile foundation in homogeneous layered soil in collapsible loess area - Zhiquan Wang; Liangliang Xin; Shuaihua Ye; Jian Wu; Weina Ye; Jingbang Li (Scientific Reports, 2025)
Abstract The collapsible nature of loess soil can lead to issues such as additional settlement of pile foundations, reduced pile strength, and decreased bearing capacity, posing a significant threat to the safety of structures in loess regions. In this paper, considering the collapsibility of loess and the layered characteristics of foundation soil, a load transfer model for single piles in homogeneous layered soil was established using the load transfer method. Simultaneously, based on the elastoplastic theory, a differential equation controlling the negative skin friction of single piles caused by the collapsibility of loess was derived. A three-linear hardening model was selected to simulate the pile–soil interface interaction. By considering the boundary conditions, the pile side friction resistance, axial force, and pile displacement were calculated, and the nonlinear patterns of load transfer for single piles in layered soil foundations were obtained. The negative skin friction characteristics of a single pile in an actual engineering project were analyzed, and the results were compared with the finite element numerical simulation to verify the rationality of the model. The research results show that in the homogeneous layered soil foundation in the collapsible loess area, the negative skin friction caused by collapsibility cannot be ignored; the calculated results of the single-pile load transfer model are in good agreement with the numerical simulation results, verifying the rationality of the model; the model successfully reveals the load transfer patterns and negative skin friction characteristics of single piles in the layered soil foundation in the collapsible loess area. This study enriches the theoretical calculation of negative skin friction for single piles in the collapsible loess area, provides a theoretical basis for calculating the negative skin friction caused by loess collapsibility, and offers a theoretical calculation method for accurately evaluating the bearing capacity of single piles in the collapsible loess areas.